Noninvasive Monitoring of Pneumococcal Meningitis and Evaluation of Treatment Efficacy in an Experimental Mouse Model - Jagath L. Kadurugamuwa; Kshitij Modi; Jun Yu; Kevin P. Francis; Carlos Orihuela; Elaine Tuomanen; Anthony F. Purchio; Pamela R. Contag (Molecular Imaging)
Noninvasive real-time in vivo bioluminescent imaging was used to assess the spread of Streptococcus pneumoniae throughout the spinal cord and brain during the acute stages of bacterial meningitis. A mouse model was established by lumbar (LP) or intracisternal (IC) injection of bioluminescent S. pneumoniae into the subarachnoid space. Bacteria replicated initially at the site of inoculation and spread progressively from the spinal cord to the brain or from the brain down to the cervical part of the spinal column and to the lower vertebral levels. After 24 hr, animals showed strong bioluminescent signals throughout the spinal canal, indicating acute meningitis of the intracranial and intraspinal meninges. A decline in bacterial cell viability, as judged by a reduction in the bioluminescent signal, was observed over time in animals treated with ceftriaxone, but not in untreated groups. Mice treated with the antibiotic survived infection, whereas all mice in untreated groups became moribund, first in the IC group then in the LP group. No untreated animal survived beyond 48 hr after induction of infection. Colony counts of infected cerebrospinal fluid (CSF) correlated positively with bioluminescent signals. This methodology is especially appealing because it allows detecting infected mice as early as 3 hr after inoculation, provide temporal, sequential, and spatial distribution of bacteria within the brain and spinal cord throughout the entire disease process and the rapid monitoring of treatment efficacy in a nondestructive manner. Moreover, it avoids the need to sacrifice the animals for CSF sampling and the potential manipulative damage that can occur with other conventional methods.